Achieving specificity in an articleless language: Specificity markers in Croatian - Katunar, Daniela (Array, 2013)
The main goal of the paper was to detect specificity markers in Croatian. As specificity is in a close relation to (in)definiteness, markers of (in)definiteness such as articles are standardly used as indicators of specificity as well. However, detecting specificity in articleless languages becomes less straightforward. Regardless of the lack of the article system, other (in)definiteness markers exist in Croatian. Here, we focused on the following markers of (in)definiteness in order to find specificity markers: i) the adjectives, ii) the numeral jedan ’one’, and iii) the demonstrative (definite) and indefinite pronouns. As specificity markers in Croatian we discuss the numeral jedan ’one’, the indefinite pronoun neki ’some’ and the construction taj + neki ’that some’. Our study also lead to the formation of three categories of specificity based on the properties of these markers: a) contextual specificity, b) semi–lexicalized specificity and c) constructional specificity.